Hydropower Development in India - Varma, CVJ; Sharma, Tanushree (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not Available. DOI: http://dx.doi.org/10.3126/hn.v14i0.11246 HYDRO Nepal Journal Journal of water Energy and Environment Volume : 14, 2014, January Page: 13-15